A Numerical Characterization of the Nanoparticles Distribution on the Surface of a Semiconductor - Rudolfova, Zdena; Hoderova, Jana (Institute of Automation and Computer Science, Brno University of Technology, 2017)
The motivation for this work was to qualitatively describe the distribution of Au nanoparticles on the surface of a semiconductor. We discuss suitable mathematical characteristics which allow the uniform distribution to be distinguished from the distribution a ected by any physical phenomenon, i.e. by the repulsive force between electrically charged particles or by the influence of properties of the surface. We identify Voronoi decomposition and a statistical analysis of Voronoi cell properties as a suitable tool for this purpose.
Keywords: distribution; Voronoi diagram; hypothesis testing; Legendre ellipse; 4PL function; nanoparticles